Stability and change in dietary scores and patterns across six waves of the Longitudinal Study of Australian Children - Kerr, Jessica A; Wake, Melissa; Mensah, Fiona K; Gasser, Constantine E (My University, 2017)
This study aimed to derive and compare longitudinal trajectories of dietary scores and patterns from 2-3 to 10-11 years and from 4-5 to 14-15 years of age. In waves two to six of the Baby (B) Cohort and one to six of the Kindergarten (K) Cohort of the population-based Longitudinal Study of Australian Children, parents or children reported biennially on the study child's consumption of twelve to sixteen healthy and less healthy food or drink items for the previous 24 h. For each wave, we derived a dietary score from 0 to 14, based on the 2013 Australian Dietary Guidelines (higher scores indicating healthier diet). We then used factor analyses to empirically derive dietary patterns for separate waves. Using group-based trajectory modelling, we generated trajectories of dietary scores and empirical patterns in 4504 B and 4640 K Cohort children. Four similar trajectories of dietary scores emerged for the B and K Cohorts, containing comparable proportions of children in each cohort: 'never healthy' (8·8 and 11·9 %, respectively), 'moderately healthy' (24·0 and 20·7 %), 'becoming less healthy' (16·6 and 27·3 %) and 'always healthy' (50·7 and 40·2 %). Deriving trajectories based on dietary patterns, rather than dietary scores, produced similar findings. For 'becoming less healthy' trajectories, dietary quality appeared to worsen from 7 years of age in both cohorts. In conclusion, a brief dietary measure administered repeatedly across childhood generated robust, nuanced dietary trajectories that were replicable across two cohorts and two methodologies. These trajectories appear ideal for future research into dietary determinants and health outcomes.
British Journal of Nutrition
Keywords: Health and wellbeing; Health and wellbeing